2011
DOI: 10.1016/j.pneurobio.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The environment and susceptibility to schizophrenia

Abstract: In the present article the putative role of environmental factors in schizophrenia is reviewed and synthesized. Accumulating evidence from recent studies suggests that environmental exposures may play a more significant role in the etiopathogenesis of this disorder than previously thought. This expanding knowledge base is largely a consequence of refinements in the methodology of epidemiologic studies, including birth cohort investigations, and in preclinical research that has been inspired by the evolving lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
420
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 577 publications
(432 citation statements)
references
References 364 publications
(434 reference statements)
6
420
0
6
Order By: Relevance
“…In addition to the strong genetic component environmental risk factors also play an important role (Van Os and Kapur, 2009;Ripke et al, 2011). In schizophrenia, this is supported by studies showing geographical variations in incidence (McGrath et al, 2004) and increased risks associated with pregnancy/delivery complications, urbanicity, migration, cannabis use and early traumatic experiences (Cantor-Graae, 2007;Schlossberg et al, 2010;Brown, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…In addition to the strong genetic component environmental risk factors also play an important role (Van Os and Kapur, 2009;Ripke et al, 2011). In schizophrenia, this is supported by studies showing geographical variations in incidence (McGrath et al, 2004) and increased risks associated with pregnancy/delivery complications, urbanicity, migration, cannabis use and early traumatic experiences (Cantor-Graae, 2007;Schlossberg et al, 2010;Brown, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…This approach is inspired by the general notion that the development of psychiatric disease may result from the interplay between the (genetically determined) susceptibility of an individual and the expose to environmental stressors (Brown, 2011), and follows previous studies, which examined whether physiological markers can predict the individual degree of psychotic symptoms in drug-induced psychosis and schizophrenia (Corlett et al, 2006;Honey et al, 2008;Krystal et al, 2003;Umbricht et al, 2002). Here, we found that the MMN slope under placebo showed a negative correlation with the subsequent ketamine-induced extent of cognitive impairments across subjects; in contrast, no comparable relationship was found for psilocybin.…”
Section: S-ketamine-induced Cognitive Impairmentsmentioning
confidence: 99%
“…There is evidence that prenatal maternal immune activation (MIA) (Brown and Derkits, 2010), perinatal hypoxia (Cannon et al, 2002;Schmidt-Kastner et al, 2012), adolescent cannabis use (Arseneault et al, 2004;Henquet et al, 2008), stress (Norman and Malla, 1993), obstetric complications (Dalman et al, 1999), urbanicity (Vassos et al, 2012), migrant status (Cantor-Graae and Selten, 2005), advanced paternal age (Malaspina, 2001), and others (Brown, 2011;Tandon et al, 2008) interact with predisposing genetics to increase risk for illness.…”
Section: Introductionmentioning
confidence: 99%